2012
DOI: 10.1371/journal.pone.0044092
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Repaired but Did Not Prevent Gentamicin-Induced Acute Kidney Injury through Paracrine Effects in Rats

Abstract: This study evaluated the effects of bone marrow-derived mesenchymal stem cells (BMSCs) or their conditioned medium (CM) on the repair and prevention of Acute Kidney Injury (AKI) induced by gentamicin (G). Animals received daily injections of G up to 20 days. On the 10th day, injections of BMSCs, CM, CM+trypsin, CM+RNase or exosome-like microvesicles extracted from the CM were administered. In the prevention groups, the animals received the BMSCs 24 h before or on the 5th day of G treatment. Creatinine (Cr), ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(215 citation statements)
references
References 32 publications
(34 reference statements)
6
200
0
7
Order By: Relevance
“…63 A similar finding was described in a gentamicin-induced model of AKI. 64 The therapeutic effect of EVs from other types of stem cells has also been described. 65 Injection of EVs derived from endothelial progenitor cells in a rat model of AKI (ischemia reperfusion Column 2 shows scatter of the laser of these same cells seen in column 1.…”
Section: Akimentioning
confidence: 99%
“…63 A similar finding was described in a gentamicin-induced model of AKI. 64 The therapeutic effect of EVs from other types of stem cells has also been described. 65 Injection of EVs derived from endothelial progenitor cells in a rat model of AKI (ischemia reperfusion Column 2 shows scatter of the laser of these same cells seen in column 1.…”
Section: Akimentioning
confidence: 99%
“…Bone-marrow-derived mesenchymal stem cells (BMSCs) have been reported to be able to treat numerous types of disease in animals, including acute kidney failure (8), ischemic heart disease (9), lung injury (10) and intracerebral hemorrhage (11) tissues in response to damage, including necrosis (12), hypoxia (13) and ischemia (14). The mechanisms by which BMSCs alleviate acute liver injury involve challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were recorded by previous investigators [13] , who stated that even after administration of high consecutive doses of CM, no improvement had been observed in animal models of ischemia reperfusion kidney injury. On the contrary, other researchers reported that CM improved renal function and increased survival in AKI experimental models [37] .…”
Section: Discussionmentioning
confidence: 91%
“…Treatment of animals with these exosomes significantly induced cellular proliferation and inhibited the tubular necrosis [37] .…”
Section: Discussionmentioning
confidence: 95%